THE ROLE OF GAPOKTAN TANI MANDIRI IN THE IMPLEMENTATION OF THE OIL PALM SMALLHOLDER REPLANTING PROGRAM IN LAUT TADOR VILLAGE - Nur Khotimah; Tuty Ningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The Oil Palm Smallholder Replanting Program (PSR) is a strategic government policy to improve the productivity of smallholder oil palm plantations by replacing aging plants with superior certified seedlings. The implementation of this program requires strong farmer institutional support, particularly through the Farmers Group Association (Gapoktan). This study aims to analyze the role of Gapoktan Tani Mandiri in implementing the PSR Program in Laut Tador Village, Batu Bara Regency. A descriptive qualitative approach was used with 17 informants: 3 Gapoktan administrators selected through purposive sampling and 14 PSR participant farmers through snowball sampling. Data were collected via observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model. Results show that Gapoktan Tani Mandiri actively performed a substantial role  four aspects: (1) program socialization conducted in 3–4 official meetings using a tiered communication mechanism; (2) administrative assistance that successfully validated 82 farmers with 123.13 hectares of land through document management and BPDPKS submission; (3) implementation coordination involving Plantation Office, PT. Paya Pinang Group, and Sucofindo; and (4) participatory evaluation through periodic group deliberations and monthly field visits. Key challenges include farmer hesitancy, repeated SMART-PSR platform changes causing 5–6 revision cycles, and slow processing by Provincial Sucofindo.